1980
DOI: 10.1073/pnas.77.9.5327
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of proliferation and differentiation of paired daughter cells: action of granulocyte-macrophage colony-stimulating factor on granulocyte-macrophage precursors.

Abstract: Mouse granulocyte-macrophage progenitor cells were stimulated to divide by the granulocyte-macrophage colony-stimulating factor (GM-CSF). The two daughter celis were separated; one daughter was transferred to medium containing a high concentration of GM-CSF, the other to medium containing a low concentration. Daughter cell-derived clones in the presence of 2500 units of GM-SF had average cell cycle times 3.5 + 2.5 (SEM) hr shorter than clones derived from the paired daughter cell stimulated by 50 units of GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(52 citation statements)
references
References 6 publications
6
44
0
2
Order By: Relevance
“…The solid line represents the TPO threshold distribution for the total MK progenitor population. The 95% confidence intervals (95% CIs) of TPO50 were 2.68 to 9.04 pg/mL (total MK), 0.62 to 2.55 pg/mL (1 MK), 3.36 to 9.32 pg/mL (2 MKs), 13 In view of the association between high responsiveness and loss of proliferative potential, a comparison was made of the CD34 ϩ CD41 ϩ CD42a ϩ and CD34 ϩ CD41 ϩ CD42a Ϫ fractions separated by cell sorting from the CD34 ϩ CD41 ϩ megakaryocyte progenitor population. Figure 6 (left panel) shows that compared with the CD42a Ϫ fraction, the CD42a ϩ fraction was shifted toward the generation of smaller-sized clones (chi-square ϭ 108, P Ͻ .001) and produced twice as many single megakaryocyte clones (64% versus 33%).…”
Section: Variations In the Number Of Doublings Account For Most Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid line represents the TPO threshold distribution for the total MK progenitor population. The 95% confidence intervals (95% CIs) of TPO50 were 2.68 to 9.04 pg/mL (total MK), 0.62 to 2.55 pg/mL (1 MK), 3.36 to 9.32 pg/mL (2 MKs), 13 In view of the association between high responsiveness and loss of proliferative potential, a comparison was made of the CD34 ϩ CD41 ϩ CD42a ϩ and CD34 ϩ CD41 ϩ CD42a Ϫ fractions separated by cell sorting from the CD34 ϩ CD41 ϩ megakaryocyte progenitor population. Figure 6 (left panel) shows that compared with the CD42a Ϫ fraction, the CD42a ϩ fraction was shifted toward the generation of smaller-sized clones (chi-square ϭ 108, P Ͻ .001) and produced twice as many single megakaryocyte clones (64% versus 33%).…”
Section: Variations In the Number Of Doublings Account For Most Of Thmentioning
confidence: 99%
“…The effects of stimulators of hematopoiesis are mediated by suppression of apoptosis and promotion of survival, [43][44][45][46][47][48] shortening of the cell cycle, 13,49,50 and retardation of differentiation. 50 The results described in the present investigation suggest that recruitment provides an additional mechanism of response to stimulators.…”
Section: Recruitment As a Mechanism For Increased Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…While GM-CSF can cause granulocyte lineage commitment at higher concentrations, it can cause monocyte lineage commitment (Metcalf 1980) at lower concentrations. Therefore, it is suggested that not only GM-CSF induces differentiation of specific myeloid cell types but also selectively guides the differentiation of a common progenitor along the granulocyte, macrophage, and DC development pathways in a concentration-dependent manner.…”
Section: Nature and Properties Of Gm-csfmentioning
confidence: 99%
“…The haematopoietic growth factor GM-CSF can maintain the survival of relatively primitive multipotential cells (Metcalf et al, , 1986 and is capable of directing the differentiation of progenitor cells down the granulocyte and macrophage lineages (Metcalf, 1980). Although the expression of GM-CSF is not detected in normal myeloid cells, GM-CSF mRNA and activity has been detected in the haematopoietic tissue from a number of patients with acute myeloid leukaemia (AML) (Young & Griffin, 1986;Young et al, 1987).…”
mentioning
confidence: 99%